Crescimento do tumor sólido de Ehrlich frente à inibição não seletiva das cicloxigenases - Brito, André Cavichioli de (2012)
Malignant neoplasms, popularly known as cancer, are characterized by autonomous and uncontrolled cell growth. The development of several human câncer is accompanied by high expression of the enzyme cyclooxygenase (COXs) responsible for the generation of various metabolites such as prostaglandins, and subsequent modulation of inflammatory chemical mediators. The aim of this study was to evaluate the effect of treatment with non-selective cyclooxygenase inhibitor on the development of solid Erhlich tumor, in periods of seven, fourteen and twenty-one days of treatment, correlating with tumor development, fibrosis and involvement of macrophages . After the evaluation period, the animals were euthanized, the tumor removed and routinely processed for HE staining for analysis of total area, area of necrosis and parenchyma. For evaluation of collagen type I, VEGF, and macrophages was used immunohistochemistry. The nonselective inhibition of cyclooxygenases resulted in significant reduction in total area to 14 days (14 days = 2.81 ± 0.85), an increase in dimension of necrotic area at 14 days of treatment (14 days = 2.25 ± 2.32 mm2), reduction in the areas parenchyma to 7:14 days of treatment (7days = 1.67 ± 1.71 mm2; 14dias = 1.70 ± 130mm2), significant reduction in collagen production after 14 days of treatment (14 days = 11.8 ± 6.2 mm2) and increased VEGF at 7 days of treatment (11.7 ± 7.0 mm2). Treatment did not affect the influx of macrophages. It can be concluded that the nonselective inhibition of cyclooxygenase was effective in controlling tumor growth in the intervening period of assessment and that in this period, the low production of collagen type I is involved in this contention, pointing to an important role of fibroblasts. However, no suggestion that macrophages are not involved, at least numerically, this containment of growth solid Ehrlich tumor. Additional studies are needed to clarify the involvement and the fact that the treatment in early stage stimulated the production of VEGF, important for the formation of a well-vascularized tissue for tumor implantation.